Manajemen Krisis Satgas Penanggulangan Bencana PT. Banten Wet Java Tourism Development - Elsi Nurfauzi; Annisarizki Annisarizki; Siska Mardiana (Indonesian Journal of Tourism and Leisure, 2021)
The purpose of this study was to determine the crisis management of PT. Banten West Java Tourism Development's post-tsunami disaster management task force. The theory used was situational of the public, using a qualitative approach with the case study method. The data collection techniques used were non-participant observation, semi-structured interviews and post-disaster documentation. tsunamis. The results of the study explained that the public focused on disasters, so the disaster management task force planned by forming a special communication team and Media Center, then working with Perum Damri Serang and the Central BMKG, as well as installing the Earthquake Early System (EEWS). Communication actions carried out by making Events and reposting Testimonials from Celebrity Endorsments. Planning and communication actions taken, to attract the public as tourists visiting for vacation in Tanjung Lesung without any sense of trauma followed by interesting events. The novelty in this study focuses more on the private sector PT Banten West Java Tourism as the main management of the Tanjung Lesung tourist area